Health Sector Sharia Shares Reaction to The Events of The 2019 Corona Virus Disease Distribution - Muhammad Irfan Yusuf (AFEBI Islamic Finance and Economic Review, 2022)
The purpose of this study was to determine the reaction of ISSI-listed health stocks to Covid-19 which was divided into three events, namely the lockdown of the city of Wuhan, the announcement of the President of the Republic of Indonesia regarding the Covid-19 case, and the WHO announcement about the virus pandemic. This study uses a quantitative approach with the event study method. Market reaction is measured by the abnormal return variable and trading volume activity. Meanwhile, the Market model is used to find the expected return with a simple linear regression analysis technique, which is then carried out by the one-sample Kolmogorov Smirnov test for normality and one sample t-test for hypothesis testing. The results of the study found that the manufacturing and service sectors were not affected by the Wuhan lockdown. Because the indicators AAR, CAAR and ATVA do not show significant results. Meanwhile, the announcement of the President of the Republic of Indonesia regarding the Covid-19 case and the announcement of the WHO pandemic virus showed that there was an influence on the manufacturing sector and health services. Because the indicators AAR, CAAR and ATVA show significant results. The results of the study found that the manufacturing and service sectors were not affected by the Wuhan lockdown. Meanwhile, the announcement of the President of the Republic of Indonesia regarding the Covid-19 case and the announcement of the WHO pandemic virus showed that there was an influence on the manufacturing sector and health services.